Evaluation of a virtual quality improvement training programme. Issue 4 (2nd April 2022) - Gupta, Poonam; Hassan, Mawahib; Thomas, Mincy; Anilkumar, Smitha; Chacko, Gracy; Shiju, Shiny; Savarimuthu, Indirani; Siddiqui, Raana; Arafa, Salah
Abstract : Background/Aims: The COVID-19 pandemic challenged not only global healthcare systems, but also educational systems, with many large, in-person training programmes being suspended. Instead, virtual learning platforms have been used, with promising results. This study explored the effectiveness of a virtual quality improvement training programme in a healthcare setting. Methods: A 6-week interprofessional virtual quality improvement training programme was developed and delivered to a total of 137 participants across three cohorts. Pre- and post-programme surveys were administered to assess knowledge gained from training. Focus groups were also conducted for more in-depth feedback about the sessions. Information was then collected regarding any quality improvement projects participants had undertaken after completing the training. Results: Mean scores were higher in the post-programme than the pre-programme survey across all knowledge domains ( P <0.001, Cohens d=6.63). Over 80% of participants reported that the training improved their understanding of and confidence in undertaking a quality improvement project, and that they would recommend the training to their colleagues. Participants went on to either lead or contribute to a variety of quality improvement projects across a wide range of specialisms. Conclusions: The virtual quality improvement training programme is an effective method of teaching, leading to participants being able to demonstrate competency in quality improvement. This approach to training delivery represents an efficient alternative to in-person training for building capability in frontline healthcare staff.